Influence of alumina on physical properties of an industrial zinc–copper smelting slag Part 2 – apparent density, surface tension and effective thermal diffusivity. (March 2013) - Mostaghel, S; Matsushita, T; Samuelsson, C; Björkman, B; Seetharaman, S
Abstract : Apparent density, surface tension and effective thermal diffusivity of an industrial iron–silicate based slag and mixtures of this slag with 5, 10 and 15 wt-% alumina addition were measured using the sessile drop and the laser flash techniques respectively. A comparison is made between corresponding values obtained from the commonly applied models and the experimental measurements. Results show that increasing the alumina concentration in slag increases the degree of polymerisation of the melt and, consequently, its effective thermal diffusivity. By alumina addition to the system, the surface tension increases progressively from 338 mN m −1, in the reference slag sample, to 488 mN m −1 in the mixture of slag and 15 wt-% alumina addition. The apparent density of the liquid–solid containing slag is continuously decreased due to the increased alumina concentration. However, the effect is more pronounced between 8 and 12 wt-% total alumina content in the slag.